MODÉLISATION DE LA DISTRIBUTION SPATIALE DES PARAMÈTRES BIOCLIMATIQUES DANS LA REGION TANGERTETOUAN (RIF OCCIDENTAL) - Abdelilah, Ghallab; Lahcen, Taiqui (European Scientific Journal, ESJ, 2015)
This work focuses on mapping the main bioclimatic factors in the region of Tangier -Tetouan (western Rif) in Morocco. This is with the view of integrating them into the modeling of the potential distribution of native plant species. These factors include the Annual Mean precipitation (Pmoy), Annual Mean Temperature (Tmoy), mean maximum temperature of the hottest month (Tmin), and the mean minimum temperature of the coldest month (Tmax). The adopted technique is the statistical modeling, which allows us to estimate such factors based on topographic and geographic variables. The backward stepwise multiple regression method which was applied, and the deterministic models obtained, have been corrected by the stochastic components that were interpolated by the Inverse Distance Weighting (IDW). The results of this modeling are discussed in the light of the results of other works of the same theme, as compared to previous descriptions of the climatic environment in the area. The results are satisfactory in the case of the average annual precipitation, mean annual temperature, and the mean minimum temperature of the coldest month, with coefficients of determination (R²) of 0,76, 0,97 and 0,74, respectively. However, this ratio reached its lowest value (0,55) for the average of the maximum temperature of the warmest month. The assessment of the accuracy of the results obtained for the mean annual precipitation and mean annual temperatures was performed by calculating the Mean Absolute Error (MAE) and the Root Mean Squared Error (RMSE). These tests have shown that stochastic components contribute significantly to the improvement of deterministic models